Использования древесных отходов - Eriomin S. S. (Scientific studies: theory, methodology and practice, 2018)
On the territory of the Krasnoyarsk Territory, the problem of utilization of wood waste is one of the most urgent, since at present almost half of the biomass of a tree is lost during processing, which naturally indicates a low level of technological processes of wood processing.
Keywords: лес; wood; отходы лесопиления; sawmill waste; sawdust; опилки